Special Aspects of the Pathohistological Diagnostics of Familial Shar-Pei Amyloidosis - Sotnikova, Elena D. (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: Familial Shar-Pei amyloidosis is an autoinflammatory systemic disease characterized by pathological synthesis of the fibrillary protein in the cells of the reticuloendothelial system, followed by amyloid formation. The purpose of our research is mainly focused on the investigation of specific structural histological changes in kidneys, liver, and spleen of the Shar-Pei dogs suffering from familial amyloidosis. Materials and Methods: The studies included autopsy and post-mortem examination of the Shar-Pei dogs with the presumptive diagnosis of familial amyloidosis or other diagnoses. Samples of kidney, liver, and spleen tissues of all cadavers were collected for histological examination. Results: Our studies showed that amyloid was formed within the ground substance of the connective tissue. Early amyloid deposits were observed in the spleen samples, providing the pathomorphological marker of the initial stage of the process generalization, whereas during the later stages, amyloid was found in kidneys, liver, and myocardium. Gradually increasing amyloid deposits lead to compression and atrophy of the parenchymal cells, sclerosis, and multiple organ dysfunction syndrome, manifesting as a wide range of clinical signs. Discussion: As a result of the conducted post-mortem examination, we have revealed systemic amyloidosis in the cadavers of the animals, initially admitted with various pathologies, which proves the importance and relevance of timely diagnostics, detection of clinical manifestations, and latent forms of the condition. Histological examination is one of the most accurate diagnostic methods for this pathology.